1999
DOI: 10.1002/(sici)1521-4141(199909)29:09<2715::aid-immu2715>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

T cell lines specific for polyomavirus T-antigen recognize T-antigen complexed with nucleosomes: a molecular basis for anti-DNA antibody production

Abstract: We have previously demonstrated that in vivo expression of the polyomavirus DNA-binding T-antigen initiated production of IgG antibodies to T-antigen and to DNA, but not to a panel of autoantigens not related to nucleosomes, indicating an antigen-selective T cell-dependent B cell response. In this study, we demonstrate that CD4-positive T cells from both normal and systemic lupus erythematosus (SLE) patients readily proliferate in response to pure T-antigen, and also to T-antigen in complex with nucleosomes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(72 citation statements)
references
References 0 publications
8
64
0
Order By: Relevance
“…Previously, we have demonstrated that nucleosomes complexed with the polyomavirus-encoded DNA-binding protein large T-Ag have the potential to induce anti-DNA Abs (12)(13)(14). Because nucleosomes alone did not induce anti-dsDNA Abs or activated nucleosome-specific T cells in normal individuals (14 -16), this directly demonstrated that nucleosomes were rendered immunogenic upon complex formation with T-Ag.…”
mentioning
confidence: 81%
“…Previously, we have demonstrated that nucleosomes complexed with the polyomavirus-encoded DNA-binding protein large T-Ag have the potential to induce anti-DNA Abs (12)(13)(14). Because nucleosomes alone did not induce anti-dsDNA Abs or activated nucleosome-specific T cells in normal individuals (14 -16), this directly demonstrated that nucleosomes were rendered immunogenic upon complex formation with T-Ag.…”
mentioning
confidence: 81%
“…Nucleosomes and laminin isoforms and chains were purified as described elsewhere (13)(14)(15). Briefly, nucleosomes were prepared from BALB/c mouse fibroblasts, disrupted by freezing and thawing, and then sheared by aspiration through a thin needle.…”
Section: Methodsmentioning
confidence: 99%
“…Heparan sulfate was obtained from Seikagaku Kogyo (Tokyo, Japan), and calf thymus dsDNA, chicken ␣-actinin, and bovine DNase I were obtained from SigmaAldrich. Nucleosomes were prepared from BALB/c spleen cells and were shown to be of similar size and composition as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE and Western blotting were performed by standard procedures (26). H1 and ␣-actinin (both applied at 2 g/well) or serially diluted homogenized kidney samples (40-45 g protein/well) were mixed with SDS-sample buffer.…”
Section: Methodsmentioning
confidence: 99%